The Theoretical Analysis of Psychological Factors that Influence the Formation of Tolerance - Huba, Natalia; Hladkykh, Zhanna (Psychological Prospects Journal, 2018)
This article is devoted to the study of the problem of the formation of a tolerant personality, which is very relevant nowadays. The tolerance is chosen as a subject of the study because it has become an integral element of the modern understanding of freedom, which is the highest human value. It is indicated that the basis of tolerance is the openness of a thought in communication and human rights. The theoretical analysis of psychological factors is made, the scientific approaches of Ukrainian and foreign scientists to the study of the features of personality tolerance, to the clarification of the essence of tolerance and its place in the social consciousness and self-consciousness are analyzed. The essence of tolerance is revealed and such concepts as correctness, acceptance and empathy are analyzed. The ways and means of tolerance forming, its psychological bases are determined. The article describes the levels of development of the main types of tolerance. It is noted that with the development of civilizations the sphere of significance in a person and society expends: the new grounds for indifference appear, the leading manifestations of which are tolerance and intolerance. The concept of intolerance is analyzed, we can say that it is based on the so-called scales according to M.Matskovsky’s theory. It was also important to distinguish different groups of tolerance factors that operate at different levels – macro, meso, and micro levels. It is determined that tolerance is a purposeful organization of positive experience, that is, the purposeful creation of conditions that require interaction with others, no matter what they are in the eyes of the subject. The conclusions are made and the prospects for further research are established.
Keywords: tolerance; intolerance; communicative behavior; moral restraint; emotional stability; personality; mechanism of tolerance